Longan syrup with lingzhi mushroom extract: Evaluation of safety and efficacy on immune and inflammatory modulation in healthy adults - Ariya Sarikaphuti,; Supamas Napavichayanun,; Thanchanit Thaipitakwong,; Piyanuch Roskhrua,; Pornanong Aramwit, (Agriculture and Natural Resources, 2021)
A longan (Dimocarpus longan Lour) syrup with lingzhi mushroom (Ganoderma lingzhi) extract was developed as a sweetener rich in bioactive constituents because of their excellent bioactivities. First, a single-dose, crossover experiment was conducted in healthy adults (n = 20) to determine postprandial glucose excursion over 2 hr following consumption of the syrup. Second, a 12 wk prospective, single-group study was used to preliminarily evaluate the effects on glycemic control, hepatic and renal functions and immune and inflammatory responses to the syrup in healthy persons (n = 8). Fasting plasma glucose, glycated hemoglobin, hepatic enzymes, blood urea nitrogen, creatinine, immunoglobulins (Igs) and C-reactive protein (CRP) were measured at baseline and weeks 4, 8 and 12. The syrup increased postprandial glucose to a lesser extent than 50 g glucose solution, with the incremental area under the curve (iAUC) of blood glucose of 327.83 ± 19.81 mg/dL.hr versus 384.08 ± 28.28 mg/dL.hr, respectively (p < 0.05). Although the syrup was classified as a high-glycemic index food (glycemic index = 85.35), daily consumption of the syrup had no significant effect on blood glucose. Hepatic and renal functions did not change significantly throughout the study. No significant alterations in Igs and CRP were observed. However, the individual-level analysis identified strong indications of improvement in immunoglobulin G and CRP at the end of the study. The results showed the beneficial effects on immune and inflammatory responses of longan syrup with lingzhi mushroom extract without adverse effects on the glycemic profile nor on the hepatic or renal functions, suggesting the health-promoting potential of this novel syrup.